Optimization of the 3D Printing Parameters on Dimensional Accuracy and Surface Finishing for New Polyamide 6 and Its Composite Used in Fused Deposition Modeling (FDM) Process / Tuan Noraihan Azila Tuan Rahim...[et al.] - Tuan Rahim, Tuan Noraihan Azila; Md Akil, Hazizan; Abdullah, Abdul Manaf; Mohamad, Dasmawati; Ahmad Rajion, Zainul (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Currently, 3D printing is emerged as one of the attractive manufacturing option to build intricate parts without human intervention. However, the users must be aware of the inherent printer’s limitation, particularly related with geometric tolerance of printed materials. This study aims to determine the optimum parameters to fabricate polyamide 6 and filled polyamide through fused deposition modeling (FDM). The studied parameters including printing speed (10-100 mm/s), temperature (240-260°C) and addition of fillers (10 wt%). The rheological properties were evaluated to estimate the behaviour of polyamides through the FDM system. In order to obtain a part with achievable accuracy between the designed and actual dimension, the accuracy of printed part manufactured using production-grade FDM 3D printer by Statasys Ltd. was used as a benchmark and also assigned in a statistical equation. The surface finishing was also studied under stereomicroscope. It was found that all parameters have a substantial influence on the rheological behaviours. Generally, increasing the printing speed improves its dimensional accuracy however higher temperatures than 250°C was not desired as it lowers the melt viscosity and reduce the geometric precision. The presence of fillers modifies the rheological behavior of the materials with respect to the unfilled polymer, in which the viscosity was slightly reduced particularly at higher shear rates. It can be concluded that high geometric precision and surface finishing can be achieved if the printing settings were correctly set up especially for new materials in FDM process.